If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (m + -2) + -5 = 8 + -2 Reorder the terms: (-2 + m) + -5 = 8 + -2 Remove parenthesis around (-2 + m) -2 + m + -5 = 8 + -2 Reorder the terms: -2 + -5 + m = 8 + -2 Combine like terms: -2 + -5 = -7 -7 + m = 8 + -2 Combine like terms: 8 + -2 = 6 -7 + m = 6 Solving -7 + m = 6 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + m = 6 + 7 Combine like terms: -7 + 7 = 0 0 + m = 6 + 7 m = 6 + 7 Combine like terms: 6 + 7 = 13 m = 13 Simplifying m = 13
| 7.2+10= | | y=x^2+8x+21 | | 72/10= | | -17r=306 | | 1.68j+1.24=13 | | (1/3x)+((6x-9)/3x)=(3x-3)/4x | | 24*4= | | 3/4t+7/8t=39 | | 5-2m=3m-5 | | 4x+9y=2 | | 72/3*4-2+10=-6 | | 20b^2-245= | | 14-y=1 | | 0.20x+0.45(50)=36.5 | | h+|-8|=15 | | 2n/-5=4/6 | | 8x+7=-3+5x+19 | | 2(d+7)-(3d+5)=2d+(4d-9+3d)-(d+3) | | 1.50m+5=15.50 | | -2/3r+2r=6/5r+8/5 | | 4(3r+2)-2r=-10 | | 0.50f+5=11.50 | | -8(r+5)=-18-8r | | 3=8x+4 | | -6(2+7k)=-12+4k | | 2(n-2)=2+4n | | 4(3n-2)=64 | | -16+3y=4 | | -2=-2-3(4-2k) | | 10k+3=8k+27 | | 72=6(-2+7x) | | 55=18+0.004x |